Local Study of blaCTX-M genes detection in Proteus spp. by using PCR technique - Passat , Dimah Nazar Faraj (Iraqi Journal of Science, 2022)
In this study, 25 clinical isolates of Proteus spp. were collected from urine, wounds and burns specimens from different hospitals in Baghdad city, all isolates were identified by using different bacteriological media, biochemical assays and Vitek-2 system. It was found that 15 (60%) isolates were identifies as Proteus mirabilis and 10 (40 %) isolates were Proteus vulgaris. The susceptibility of P. mirabilis and P. vulgaris isolates towards cefotaxime was (66.6 %) and (44.4 %) respectively; while the susceptibility of P. mirabilis and P. vulgaris isolates towards ceftazidime was (20%). Extended spectrum β-lactamses producing Proteus was (30.7 %). DNA of 10 isolates of P. mirabilis and 4 isolates of P. vulgaris were extracted and detection of (blaCTX-M-1, blaCTX-M-2, blaCTX-M-8 and blaCTX-M-9) was done by multiplex polymerase chain reaction (PCR). Results showed the presence of blaCTX-M-2 gene, which is responsible for resistance to cefotaxime in these isolates, while no other types of , blaCTX-M genes were found in them.